Using Digital Technologies In Implementing The Fundamentals Of Economy (Eurasian Journal of History, Geography and Economics, 2026)
This article analyzes the role of digital economy in Uzbekistan and its impact on the economy. Digital technology and innovations create opportunities to bring the economy of Uzbekistan to a new level, as well as increase production efficiency, improve public management, and strengthen competitiveness. The article explores the importance of existing infrastructure, information technology and public policy for the development of the digital economy. The study analyzed the current state of the Digital Economy, Opportunities and problems in Uzbekistan